The Phenomenon of Trust in Flat Owners’ Collective Renovation Strategies in Estonia - Ojamäe, Liis; Paadam, Katrin (Studies of Transition States and Societies, 2015)
Mobilising flat-owners into renovating residential blocks in post-socialist countries has been a complicated process. Evidence from Estonia show that the success of collective renewal strategies depends not only on economic issues but also on ways investments are organised and, significantly, the relationship of trust between different actors. The paper aims at conceptualising the issue of institutional trust upon the experience of urban housing renewal in Estonia. It is contended that trust is crucial for the joint decision-making in a block as well as for facilitating negotiations between flat-owners associations, local municipalities and market actors. The paper draws on three qualitative studies conducted in Estonia during the 2000s which allow asserting that trust towards new strategies of housing renewal can be achieved and maintained by ‘best practices’, which by concentrating expert knowledge also denote direct communication between experts and flat-owners. While it is important to raise the residents’ technical knowledgeability, it is indispensable to develop abilities to manage and communicate the renovation process between different parties. The public sector is conceived to be a central actor in sustaining trust between actors who have no previous positive experience from collective residential strategies.